Effectiveness Mentoring Sharia Cooperatives in Increase Literacy Finance for Micro Business Actors - Diana Maghfiroh (Sekolah Tinggi Agama Islam Kuningan, 2024)
Study This aiming for evaluate effectiveness of mentoring programs cooperative sharia in increase literacy finance for perpetrator business micro in Indonesia. Approach quantitative descriptive used with method survey of 150 actors’ business micro that has been accept mentoring for at least six months in some city large in Indonesia, including Jakarta, Bandung, Surabaya, Yogyakarta, and Medan. The results of the study show improvement significant in literacy finance, which includes understanding base about management finance, skills recording cash flow, and planning term long. Analysis statistics descriptive and paired sample t-test revealed improvement literacy finance by 20% to 25% after assistance, with variations influenced by factors​ access technology and support infrastructure in the area urban and also rural. Research this also found that cooperative sharia plays a role important in provide education appropriate financial​ with needs and characteristics perpetrator business micro. However, the challenges like limitations internet access and power companion in rural areas Still need overcome for optimize program effectiveness. Recommendations main study This is expand digital access and improve training for companion cooperative sharia use support improvement literacy and sustainability business micro in a way more area. Findings This give contribution for development policy cooperative in strengthen inclusion and literacy finance among​ perpetrator business micro in Indonesia.